Being and becoming a state: the statebuilding and peacebuilding conversations in southern Somalia and Somaliland. Issue 1 (2nd January 2021) - Ingiriis, Mohamed Haji
ABSTRACT: Using contemporary and historical approaches, this paper empirically interrogates the recent and current trajectories of the statebuilding and peacebuilding processes and politics of southern Somalia (recognised as a state) and Somaliland (unrecognised as a state). To understand how the (post-)violent politics has preconditioned the form and face of becoming a Weberian state, the paper traces the internal dynamics and external dimensions of the two entities. In so doing, it offers empirical and theoretical contributions as to why the attempts at statebuilding and peacebuilding conversations in southern Somalia fail from time to time while Somaliland by contrast appears to be different. Although comparisons and contrasts between the two entities have been varied from the outset, there are similarities as well as differences in terms of structural differences, state differentiations, competing actors, different stakes and similar practices of clan politics. If evaluating institutions and actors in the longue durée approach suggests why a state is a state in Somaliland but not in southern Somalia, assessing both the state structures and the stakes involved reveals why power struggle and resource competition have become violent in one entity but not the other. Based on research data collected mainly in southern Somalia and Somaliland, the paper contributes to the research on the political conflicts in fragile and failed states in Africa, post-war Somali reconstruction and statebuilding and peacebuilding processes in war-torn societies.